UPAYA PENINGKATAN KOGNITIF ANAK DENGAN ALAT PERMAINAN EDUKATIF POHON ANGKA - Aushafil Karimah; Holifatus Sa’diah (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Universitas Ibrahimy, 2022)
This study aims to describe and find out the results of the use of number tree APE in improving children's cognitive at TK PGRI 07 Tapen. This study uses action research Arikunto's design class with 4 stages, namely: planning, implementing action, observing, and reflecting. This research is used to understand children's development and as an effort to improve children's cognitive abilities. The conclusion of this study is that children are able to count 1-10 well, can point to numbers and sort numbers, mention colors and shapes. The results of the cognitive improvement of children using the number tree educational game tool at TK PGRI 07 Tapen Bondowoso are: In the initial pre-cycle observation, the average score was 4.1 and the percentage of classical completeness was 26.1%. Based on the results of the first cycle, children's cognitive improvement with the number tree educational game tool has not been considered successful, as evidenced by twenty-three children only twelve children are categorized as complete, with an average score of 4.6 and a percentage value of classical completeness 52.2% . In the results in the second cycle, the children's learning completeness was said to be successful, as evidenced by the twenty-three children, twenty of them were said to be complete with an average score of 5.2 and the percentage of classical completeness was 86.9%.